PENGARUH KEBIJAKAN DIVIDEN SEBAGAI VARIABEL PEMODERASI DARI HUBUNGAN KINERJA KEUANGAN DAN KINERJA PASAR TERHADAP NILAI PERUSAHAANPADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA(2011 - 2015) - Vedy Vedy; Susi Dwimulyani; Bayu Dewangkoro (Jurnal Magister Akuntansi Trisakti, 2016)
The purpose of this research is to investigate and analyze the effect of financial and market performance (net profit margin, debt to equity ratio, current ratio, price earning ratio, economic value added, and market value added) to firm value in manufacturing companies listed on the Stock Exchange Indonesia, as well as to indentify and analyze whether the dividend policy (dividend payout ratio and dividend yield) as a moderating variable affect correlation variable of net profit margin, return on equity, debt to equity ratio, current ratio, price earning ratio, economic value added, dan market value added to firm value. Population of this research amount to 143 companies which were manufacturing company listed on the Indonesia Stock Exchange the year 2011-2015. Sample selected by using method of purposive sampling amount to 26 companies. Data was processed using the method of data panel regression statistical test by using Eviews version 8.0 software. The result of this research shows that (1) profitability ratio and dividend payout ratio affect negatively to firm value. Leverage, liquidity ratio, market ratio,economic value added, market value added and dividend yield affect positively to firm value. (2) Dividend policy which measured with dividend payout ratio is able to moderate the effect of profitability ratio, leverage ratio, liquidity ratio and market ratio to firm value. Dividend policy which measured with dividend payout ratio is not able to moderate the effect ofeconomic value added and market value added to firm value. (3) Dividend policy which measured with dividend yield is able to moderate the effect of profitability ratio, market ratio, economic value added and market value added to firm value. Dividend policy which measured with dividend yield is not able to moderate the effect of leverage ratio and liquidity ratio to firm value